Mixing business and politics : Penzeys Spices - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Bill Penzey Jr., CEO of Penzeys Spices Inc., an independent retailer of spices, has a history of vocally and publicly using his company to communicate his opinions on sociopolitical issues. In recent years, the company and its CEO have been highly critical of the Trump Administration. This case provides an opportunity for students to understand the concept of corporate political activism, and to assess the pros and cons of mixing business and politics. In addition, this case asks students to consider whether the conventional wisdom about refraining from mixing business and politics remains appropriate today.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business and politics -- Case studies